2009
DOI: 10.1111/j.1440-1789.2008.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in developmental brain disorders

Abstract: Oxidative stress is one of the predisposing factors in adult neurological disorders. We have examined the involvement of oxidative stress in child-onset neurodegenerative disorders, and here we review the findings from our analysis. In cases of Cockayne syndrome, the oxidative products of lipids and proteins were increased in the globus pallidus; however, oxidative nucleotide damage that coincided with reduced copper/zinc superoxide dismutase (Cu/ZnSOD) expression was observed in cases of xeroderma pigmentosum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…In alternative, the high oxidative stress markers detected in serum of these patients may describe an epiphenomenon of unspecific stress adaptation to epileptic attacks. It has been reported that structural anomalies of brain may play a role in increasing oxidative stress markers [3]. That pathogenetic hypothesis cannot be evoked in our series of patients since all of them had normal brain MRI.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In alternative, the high oxidative stress markers detected in serum of these patients may describe an epiphenomenon of unspecific stress adaptation to epileptic attacks. It has been reported that structural anomalies of brain may play a role in increasing oxidative stress markers [3]. That pathogenetic hypothesis cannot be evoked in our series of patients since all of them had normal brain MRI.…”
Section: Discussionmentioning
confidence: 89%
“…Lipid peroxidations originating from oxidative degeneration of polyunsaturated fatty acids can migrate to different regions of cells leading to destructive processes. In addition, the loss of fatty acids results in membrane damage [3,4]. The defense mechanisms against oxidation include: (i) antioxidant enzymes such as glutathione reductase, glutathione peroxidase, superoxide dismutase and catalase; and (ii) low-molecular-weight antioxidant compounds such as albumin, uric acid, ascorbic acid, alfa-tocopherol, beta-carotene, metal chelators, glutathione, and ubiquinones [5].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress originates from an imbalance between the production of reactive oxygen species (ROS) and, to a lesser extent, reactive nitrogen species (RNS), and the antioxidant capacities of cells and organs [5]. Recently, oxidative stress was confirmed to play a role in adult-onset neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted the inverse association between the consumption of plant foods and the prevalence of noncommunicable chronic diseases such as cancer, diabetes, cardiovascular diseases and degenerative diseases [1][2][3][4][5][6] . The benefits are related to the presence of bioactive compounds with antioxidant activity, which are capable of neutralizing the so-called free radicals.…”
Section: Introductionmentioning
confidence: 99%